2019
DOI: 10.1111/bph.14692
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the forward Na+/Ca2+ exchanger suppresses the growth of glioblastoma cells through Ca2+‐mediated cell death

Abstract: Background and PurposeThe Na+/Ca2+ exchanger (NCX) working in either forward or reverse mode participates in maintaining intracellular Ca2+ ([Ca2+]i) homeostasis, which is essential for determining cell fate. Previously, numerous blockers targeting reverse or forward NCX have been developed and studied in ischaemic tissue injury but barely examined in glioblastoma for the purpose of anti‐tumour therapy. We assessed the effect of NCX blockers on glioblastoma growth and whether NCX can become a therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…NCX controls intracellular Ca 2+ homeostasis, and silencing of NCX1 isoforms diminished the effect of SKF 96365 on glioblastoma cells ( Song et al, 2014 ). In addition, inhibition of the forward NCX (Ca 2+ exit mode), with bepridil and CB-DMB, induced Ca 2+ -mediated injury in glioblastoma cells ( Hu et al, 2019 ). NCX maintains cytoplasmic calcium homeostatic levels, in addition to plasma membrane Ca 2+ transport ATPase (PMCA) and sarco/endoplasmic reticulum (SR/ER) Ca 2+ -ATPase (SERCA).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…NCX controls intracellular Ca 2+ homeostasis, and silencing of NCX1 isoforms diminished the effect of SKF 96365 on glioblastoma cells ( Song et al, 2014 ). In addition, inhibition of the forward NCX (Ca 2+ exit mode), with bepridil and CB-DMB, induced Ca 2+ -mediated injury in glioblastoma cells ( Hu et al, 2019 ). NCX maintains cytoplasmic calcium homeostatic levels, in addition to plasma membrane Ca 2+ transport ATPase (PMCA) and sarco/endoplasmic reticulum (SR/ER) Ca 2+ -ATPase (SERCA).…”
Section: Cancermentioning
confidence: 99%
“…The Na + /Ca 2+ exchanger (NCX), which maintains cytoplasmic calcium homeostatic levels, also increases Ca 2+ levels in glioblastoma cells ( Song et al, 2014 ). Inhibition of the forward NCX (Ca 2+ exit mode) induces a Ca 2+ -mediated injury in glioblastoma cells ( Hu et al, 2019 ). Finally, G protein-coupled metabotropic receptors coupled to activation of phospholipase C result in the generation of the second messenger, inositol 1,4,5 trisphosphate, which increases intracellular Ca 2+ and diacylglycerol, involved in cancer cell proliferation, with important participation of the large-conductance voltage- and Ca 2+ -activated K + channel.…”
Section: Cancermentioning
confidence: 99%
“…Human glioblastoma cell lines A172, U251 and rat glioma C6 cells were from American Type Culture Collection (ATCC) (Rockville, Maryland, USA). The pediatric glioblastoma cell line SF188 was kindly provided by Dr. Yu-Jie Tang (Shanghai Jiao Tong University School of Medicine, China) and Dr. Stefan Pfister (DKFZ, Germany) [ 30 ]. Cells were cultured in Dulbecco’s Modification of Eagle’s Medium (DMEM) (Gibco, Carlsbad, CA, USA) containing l -glutamine and 10% fetal bovine serum (FBS) (Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…In glioblastoma cells, the forward-mode NCX was shown to be predominant, since blocking the reverse mode NCX with selective inhibitors did not affect the tumor growth. It was shown that blocking the forward-mode NCX can suppress growth via Ca 2+ -mediated injury [ 37 ]. Furthermore, differently mutated melanoma cell lines (BRAF V600E -mutated and NRAS Q61R -mutated) present different Ca 2+ homeostatic status and dependence on Ca 2+ levels to survive and proliferate.…”
Section: Ncx1 In Solid Tumorsmentioning
confidence: 99%